2022
DOI: 10.4103/jehp.jehp_701_21
|View full text |Cite
|
Sign up to set email alerts
|

Determining the characteristics of a mental supportive workplace according to female hospital staff in one of Tehran hospitals

Abstract: BACKGROUND: Health-care workers are exposed to complex types of health and safety hazards. A high percentage of hospital staff in Iran are women, who in addition to heavy and stressful hospital work, also carry the burden of the family roles. It is in these circumstances that creating a supportive environment for women is of particular importance. Accordingly, this study is designed to determine the characteristics of a mental supporting work environment in the workplace from the perspective of fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This study showed that one of the important factors that could have a signi cant impact on promoting women's health in workplaces was their active participation in the development of programs and policies related to women's health. The presence of women in managerial positions is important for creating a healthy workplace for women, and their cooperation and participation in the formulation of policies and programs related to occupational health and safety can help managers understand the issues and problems faced by women, and also a representative of all groups, especially gender groups, should be present in health and safety related to committees so that a healthy workplace can be prepared for both sexes [14]. Therefore, as discussed in this study, studies also suggest that women's health can be seen in the vision and policy statements of various organizations and workplaces and can help create healthy workplaces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study showed that one of the important factors that could have a signi cant impact on promoting women's health in workplaces was their active participation in the development of programs and policies related to women's health. The presence of women in managerial positions is important for creating a healthy workplace for women, and their cooperation and participation in the formulation of policies and programs related to occupational health and safety can help managers understand the issues and problems faced by women, and also a representative of all groups, especially gender groups, should be present in health and safety related to committees so that a healthy workplace can be prepared for both sexes [14]. Therefore, as discussed in this study, studies also suggest that women's health can be seen in the vision and policy statements of various organizations and workplaces and can help create healthy workplaces.…”
Section: Discussionmentioning
confidence: 99%
“…Creating the supportive work environments for women, especially those working in environments like hospitals that bring a lot of work pressure and workload for them, can be one of the important policies for organizations and hospital work environments [14]. Working in medical centers can be exhausting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, codes were organized into sub-categories by assessing their relevance. The final step included grouping sub-categories into key categories [ 20 ].…”
Section: Methodsmentioning
confidence: 99%